CUESTIONAMIENTOS EN TORNO A LA FUNCIÓN DE LOS DICCIONARIOS EN LA SOCIEDAD - Lizano Cambronero, Ana Lucía (2012)
This work is based on the relationship of the dictionaries with the educational process in the transmission of the cultured variety of speech. In this context, it examines the role of dictionaries as records of the standard –in its descriptive sense of frequent uses in a speech community–, but also as diffusers of linguistic attitudes –which could eventually lead, within the scope of formal education, in a prescriptive sense–. Both aspects of the role of dictionaries –description and prescription– are analyzed to appraise their impact on society (linguistic attitudes, linguistic insecurity, social mobility and national unity). It also values the position of the linguist with regard to the figure of the dictionary. With respect to the lexicographical marking, draws attention to the demarcation of a distance from the rule and its implications in attitudes toward one or another variety of speech. In addition, at regard to the formation of the corpus, notes the work of the linguist in the light of the notions of «paradox of the observer» and «mesolect», raised by Lipski.